(untitled) (Annals of Medical Research, 2021)
The comorbidity of recurrent nasal polyps, non-steroidal anti-inflammatory drug hypersensitivity and chronic rhinosinusitis is called Samter’s syndrome. It is less common in childhood than in adulthood. Patients first have nasal symptoms and then asthma and non-steroidal anti-inflammatory drug (NSAID) hypersensitivity begin to accompany. For definitive diagnosis, NSAID or aspirin hypersensitivity must be shown with provocation test. In this case report, oral provocation test with ibuprofen was performed on a 17-year-old female patient who had recurrent nasal polyps and chronic rhinosinusitis accompanied by asthma and NSAID hypersensitivity and the test was found to be positive. The patient was diagnosed with Samter’s syndrome and aspirin desensitization was applied. Inhaled steroid, intranasal steroid and montelukast therapies were started. As a conclusion, although it is more common in adults, Samter’s syndrome should also be considered in pediatric patients with recurrent nasal polyp, chronic rhinosinusitis, asthma, and NSAID hypersensitivity.